Labor Market Implications of Switching the Currency Peg in a General Equilibrium Model for Lithuania - Pizzati, Lodovico (The World Bank, 2002)
On February 2, 2002, Lithuania switched its currency anchor from the dollar to the euro. While pegging to the dollar (since April 1994) has proven successful throughout the transition years, the recent decision to peg to the euro was motivated by the increasing trade relations with European economies. Pizzati does not argue which peg is more appropriate, but he analyzes the implications of changing the exchange rate regime for different sectors and labor groups. While pegging to the euro entails more stability for the export sector, Lithuania is still dependent on dollar-based imports of primary goods from the Commonwealth of Independent States, more so than other Baltic countries or Central European economies. Pizzati uses a multisector general equilibrium model to compare the effects of dollar-euro exchange rate movements under these alternative pegs. Overall, simulation results suggest that while a euro-peg will provide more stability to GDP and employment, it will also imply more volatility in prices, suggesting that under the new peg macroeconomic policy should be more concerned with inflationary pressures than before. From a sector-specific perspective, pegging to the euro will provide a more stable demand for unskilled-intensive manufacturing and commercial services. But other sectors, such as agriculture, will still face the same vulnerability to exchange rate movements. This suggests that additional policy measures may be needed to compensate sector-specific divergences. This paper—a product of the Poverty Reduction and Economic Management Sector Unit, Europe and Central Asia Region—is part of a larger effort in the region to address European Union integration issues in transition economies. Please contact Lodovico Pizzati, room H4-214, telephone 202-473-2259, fax 202-614-0683, email address lpizzati@worldbank.org